2005
DOI: 10.1109/tuffc.2005.1503960
|View full text |Cite
|
Sign up to set email alerts
|

Progress in medical ultrasound exposimetry

Abstract: Biomedical applications of ultrasound have experienced tremendous growth over the past 50 years. Early work in thermal therapy and surgery soon was followed by diagnostic imaging and Doppler. Because patient safety was an important issue from the beginning, the study of methods for measuring exposure levels, and their relationship to possible biological effects, paralleled the growth of the various therapeutic and diagnostic techniques. The diverse conditions of use have presented a range of exposure measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 160 publications
0
37
0
Order By: Relevance
“…Our previous investigation indicated that the acoustic power in continuous wave mode could be about 60-70% of the electrical power. Acoustic power measurement for the transducer was determined by the precision ultrasound power meter (Medisonics Ltd., Watford, UK) using radiation pressure technique with ±5% measure veracity [26,27]. So, the output electrical power from the amplifier was 2.0 W/cm 2 , and the acoustic power I SATA was 1.4 ± 0.07 W/cm 2 in this study.…”
Section: Ultrasound Treatment and Dosimetrymentioning
confidence: 81%
“…Our previous investigation indicated that the acoustic power in continuous wave mode could be about 60-70% of the electrical power. Acoustic power measurement for the transducer was determined by the precision ultrasound power meter (Medisonics Ltd., Watford, UK) using radiation pressure technique with ±5% measure veracity [26,27]. So, the output electrical power from the amplifier was 2.0 W/cm 2 , and the acoustic power I SATA was 1.4 ± 0.07 W/cm 2 in this study.…”
Section: Ultrasound Treatment and Dosimetrymentioning
confidence: 81%
“…Our previous investigation indicated that the acoustic power in continuous wave mode could be about 60-70% of the electrical power. Acoustic power delivered from the transducer was measured by Precision Ultrasound Power Meter (Medisonics Ltd, Watford, UK) using radiation force balance technique with ±5% measure veracity [24,25]. Therefore, the output electrical power from the amplifier is 2.0 W/cm 2 , and the acoustic power I SA-TA was 1.4 ± 0.07 W/cm 2 in this study.…”
Section: Ultrasound Treatment and Dosimetrymentioning
confidence: 92%
“…9 If the acoustic field at the point of measurement does not have a uniform planar pressure distribution over the active area of the receiver, then the true acoustic pressure at the focus can be underestimated. This effect is referred to as spatial averaging.…”
Section: Spatial Averagingmentioning
confidence: 99%
“…Although this approach is widely used in medical US, the challenge of directly measuring and modeling HIFU fields is worth revisiting since experimental tools and numerical models may improve over time, and no standard method, such as that for diagnostic US, 8 has yet been agreed upon for HIFU devices. 9 The most common parameter to characterize the acoustic output of a HIFU device is the spatially averaged intensity ͑I SAL ͒. 10 The calculation of I SAL for a given source is achieved through measurement of the acoustic power output of the device and the focal cross-sectional area of the HIFU beam.…”
Section: Introductionmentioning
confidence: 99%